FACTORS AFFECTING THE QUALITY OF ACCOUNTING INFORMATION: THE ROLE OF ACCOUNTING INFORMATION SYSTEMS - Riska Evi Yanti; Caecilia Widi Pratiwi (JRAK, 2022)
This study aims at determining the effects of organizational structure, organizational culture and user abilities on the quality of accounting information systems and the implications for accounting information quality. The research used was surveying the population of employees in the Jakarta and Tangerang areas who worked in the accounting and finance fields with samples obtained were 97 respondents. The primary data used in this study were obtained through the distribution of questionnaires, which were analyzed by using Partial Least Squares (PLS). The results suggested that the quality of accounting information systems was unaffected by the organizational structure, Meanwhile, organizational culture and user abilities had a significant effect. In addition, accounting information system quality had signficant effect on accounting information quality.